Peningkatan Pemahaman dan Berpikir Kritis melalui Model PBL Reflektif di Kelas X SMA Tarakanita - Arnanda Krisnanto; Ansel Joko Prayitno (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
The study titled "Improving Understanding and Critical Thinking Skills Through a Reflection-Based PBL Model in Class X Phase E of SMA Tarakanita 1 Jakarta" aims to investigate the effectiveness of applying a reflection-based Problem Based Learning (PBL) model in enhancing students' understanding and critical thinking skills. The background of this study stems from the fact that students were still facing learning difficulties and lacked active participation in the learning process. This Classroom Action Research (CAR) was conducted over two cycles. Cycle I focused on the topic of the Role of the Holy Spirit, while Cycle II explored the concept of the Trinity. Each cycle followed the stages of planning, action, observation, and reflection. Data collection was carried out using observation sheets, interviews, questionnaires, and understanding tests. The results indicated a significant improvement in student learning outcomes. In Cycle I, students' understanding was categorized as moderate with an average score of 75. After revisions and the application of a more refined PBL model in Cycle II, the average score increased to 95, falling into the high category. Furthermore, students demonstrated enhanced critical thinking skills, particularly in analyzing, evaluating, and relating theological concepts to real-life experiences. The findings suggest that the reflection-based PBL model is effective in fostering both cognitive understanding and reflective thinking. The study concludes that this model can be a valuable approach in Catholic Religious Education, encouraging deeper engagement and understanding of faith teachings. It is recommended for broader implementation to support students in becoming more reflective, active, and insightful learners.